The Legal Comparison of Transfer of Object Fiduciary by Debtor to Third Party without Creditor's Approval - Widhi Handoko; Bahtiyar Efendi (Jurnal Akta, 2022)
The purpose of this study is to find out about the Fiduciary provider in the Consumer Financing agreement with the Fiduciary Guarantee contained in the Fiduciary Guarantee Deed, it is forbidden to transfer the Fiduciary guarantee object to another party without the approval of the Fiduciary Recipient. This is because in Act No. 42 of 1999 concerning Fiduciary Guarantees there are provisions regarding the prohibition to transfer objects of Fiduciary guarantees without the approval of Fiduciary Recipients to provide legal protection to Fiduciary Recipients. The research in this paper is a normative law research. In the debtor's relationship with a third party, there is no legal relationship because the transfer of the fiduciary object is not valid as stated in Article 1320 of the Civil Code concerning the conditions for the validity of the agreement. Articles 35 and 36 of the UUJF also regulate criminal sanctions that reaffirm the prohibition of transferring, mortgaging, or leasing fiduciary guarantees as objects. In connection with the principle of providing legal certainty, UUJF adopts the principle of registration of fiduciary guarantees. The benefit of a fiduciary agreement made in writing is that the creditor holding the fiduciary guarantee in his interest will demand the easiest way to prove the delivery of the guarantee to the debtor.